violencia digital contra la mujer: manifestaciones en las redes sociales de estudiantes de la carrera de comunicación de la universidad técnica de machala - Castillo Gomez, Josselyn Brigitte; Flores Lanche, Naire Nicole (Machala: Universidad Tecnica de Machala, 2024)
This research addresses a growing problem of digital violence against women in the university context, specifically among female students of Communication at the Technical University of Machala, highlighting the relevance of the issue in the current digital era and its impact on society, this study seeks to diagnose the manifestations of digital violence against women in social networks within the aforementioned university context. The state of the question reveals that, although there are studies on digital violence, there is a gap in the specific research on female university students of communication in Ecuador. The methodology employed is mixed, combining quantitative (student surveys) and qualitative approaches (expert interviews and focus groups), following a two-stage model allowing a holistic understanding of the phenomenon. The results and discussion reveal the prevalence of various forms of digital violence, such as the non-consensual dissemination of private information, as well as a worrying normalization of these behaviors. The conclusions underline the urgent need to address this issue through education, awareness raising and improvement of institutional support mechanisms, highlighting the importance of denormalizing digital violence and empowering students to confront and report these acts.
Esta investigación aborda una problemática creciente de la violencia digital contra la mujer en el contexto universitario, específicamente entre las estudiantes de la carrera de Comunicación de la Universidad Técnica de Machala, destacando la relevancia del tema en la era digital actual y su impacto en la sociedad, este estudio busca diagnosticar las manifestaciones de violencia digital en contra de la mujer en las redes sociales dentro del mencionado contexto universitario. El estado de la cuestión revela que, si bien existen estudios sobre violencia digital, hay una brecha en la indagación específica sobre estudiantes universitarias de comunicación en Ecuador. La metodología empleada es mixta, combinando enfoques cuantitativos (encuestas a estudiantes) y cualitativos (entrevistas a expertos y focus group), siguiendo un modelo de dos etapas permitiendo una comprensión holística del fenómeno. Los resultados y la discusión revelan la prevalencia de diversas formas de violencia digital, como la difusión no consentida de información privada, además se evidencia una normalización preocupante de estas conductas. Las conclusiones subrayan la necesidad urgente de abordar esta problemática mediante educación, concientización y mejora de mecanismos de apoyo institucional, destacando la importancia de desnormalizar la violencia digital y empoderar a las estudiantes para enfrentar y denunciar estos actos.
Keywords: VIOLENCIA DIGITAL; REDES SOCIALES; ESTUDIANTES UNIVERSITARIAS; COMUNICACION